2021
DOI: 10.1039/d1cy01643a
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanum modified Fe-ZSM-5 zeolites for selective methane oxidation with H2O2

Abstract: Lanthanum modified Fe-ZSM-5 catalyst can both increase selective methane oxidation performance and decrease H2O2 consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…The use of the aluminosilicate ZSM-5 within methane oxidation has received considerable attention, while such studies have typically focused on biomimetic oxidation, utilizing Fe and/or Cu species incorporated into the zeolite framework in conjunction with preformed H 2 O 2 . Additionally, there has been growing attention placed on the use of ZSM-5 as a support for active metal species for both the direct synthesis of H 2 O 2 and in situ oxidation of methane to methanol . Recently Jin et al reported that enhanced rates of methane oxidation via in situ H 2 O 2 synthesis can be achieved through the introduction of a hydrophobic organo-silane layer onto the external surface of a AuPd@ZSM-5 catalyst, with the improved reactivity attributed to the increased localized concentrations of reagents (H 2 and O 2 ), and the confinement of the subsequently synthesized H 2 O 2 and CH 4 in close proximity to active sites …”
Section: Introductionmentioning
confidence: 99%
“…The use of the aluminosilicate ZSM-5 within methane oxidation has received considerable attention, while such studies have typically focused on biomimetic oxidation, utilizing Fe and/or Cu species incorporated into the zeolite framework in conjunction with preformed H 2 O 2 . Additionally, there has been growing attention placed on the use of ZSM-5 as a support for active metal species for both the direct synthesis of H 2 O 2 and in situ oxidation of methane to methanol . Recently Jin et al reported that enhanced rates of methane oxidation via in situ H 2 O 2 synthesis can be achieved through the introduction of a hydrophobic organo-silane layer onto the external surface of a AuPd@ZSM-5 catalyst, with the improved reactivity attributed to the increased localized concentrations of reagents (H 2 and O 2 ), and the confinement of the subsequently synthesized H 2 O 2 and CH 4 in close proximity to active sites …”
Section: Introductionmentioning
confidence: 99%
“…3 Subsequent extensive investigations of LPO of methane have shown that product formation on ZSM-5-based catalysts is affected by various factors, such as the methane inlet pressure, 4–6 oxidant concentration, 4–6 the solvent used, 4 reaction time, 4,5,7–9 temperature of the reaction, 4,10 catalyst amount, 4,6 metal loading 3,7–9,11,12 and acidity/hydrophobic nature of the catalyst. 12–15…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, lanthanum modification in the Fe-ZSM-5 catalyst suppressed the H 2 O 2 dissociation and enhanced the formation of liquid oxygenates. 12 This indicates the need for controlled dissociation of H 2 O 2 at the active sites for the selective formation of the desired products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24] An aqueous route using H 2 O 2 as environmentally benign oxidant has been thoroughly studied for decades. Hutchings and co-workers have made great contributions in aqueous route using H 2 O 2 as an oxidant at a low temperature on many kinds of heterogeneous substances catalysts, such as Fe-ZSM-5, [25,26] LaFe-ZSM-5, [27] AuPd/TiO 2 , [28,29] AuPdCu/TiO 2 , [30] and AuPd colloid. [31] Recently, Bao and co-workers found that graphene-confined single Fe atoms can directly convert methane into C1 oxygenates at 25 °C with a selectivity of 94 %.…”
Section: Introductionmentioning
confidence: 99%